Neural substrates of excessive daytime sleepiness in early drug naïve Parkinson's disease: A resting state functional MRI study. (March 2016) - Wen, Ming-Ching; Ng, Samuel Y.E.; Heng, Hannah S.E.; Chao, Yin Xia; Chan, Ling Ling; Tan, Eng King; Tan, Louis C.S.
Abstract: Introduction: Excessive daytime sleepiness (EDS) is a common non-motor symptom in Parkinson's disease (PD), but its neuropathology remains elusive due to the limited studies and the inclusion of medicated patients. This current study examined the neural substrates of EDS in drug naïve PD patients. Methods: A total of 76 PD patients in the early disease stages were recruited; 16 of them had EDS, while the remaining 60 did not. Resting state functional magnetic resonance imaging (rs-fMRI) was used to determine group differences (patients with EDS vs. patients without EDS) in spontaneous neural activity indicated by regional homogeneity (ReHo). Additionally, functional connectivity (FC) of the regions showing group differences in ReHo with the entire brain was performed. Results: ReHo analysis controlling for gray matter volume, age, gender, general cognition, depression, postural instability gait difficulty, and rapid eye movement sleep behavior disorder showed decreased ReHo in the left cerebellum and inferior frontal gyrus, but increased ReHo in the left paracentral lobule in PD-EDS patients, compared with patients without EDS. FC analysis controlling for the same variables as in the analysis of ReHo revealed that the three regions showing ReHo differences had decreased FC with regions in the frontal, temporal, insular and limbic lobes and cerebellum in PDs with EDS. Conclusion: While decreases in ReHo and FC were found, increases in ReHo were also noted, implying both neural downregulation and compensatory mechanisms in early PD patients with EDS. Longitudinal studies are warranted to clarify the long-term impact of EDS in PD. Highlights: PDs with EDS showed decreased regional homogeneity (ReHo) and FC in the left frontal and cerebellar areas. PDs with EDS also showed increased ReHo in the left paracentral lobule. Neural downregulation and compensations were noted in early PD patients with EDS.